2000
DOI: 10.1046/j.1526-4610.2000.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type A as a Migraine Preventive Treatment

Abstract: Objective.-To assess the safety and efficacy of botulinum toxin type A (BOTOX; Allergan, Inc) in the prevention of migraine.Background.-Current migraine preventive therapies are often unsatisfactory because of their limited efficacy, adverse effects, and drug interactions. Botulinum toxin type A injections often reduce the pain associated with conditions such as cervical dystonia, achalasia, rectal fissures, and myofascial pain syndrome. An open-label, noncontrolled study of botulinum toxin type A suggested be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
284
2
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 486 publications
(303 citation statements)
references
References 9 publications
8
284
2
9
Order By: Relevance
“…A peripheral antinociceptive effect of the neurotoxin has been suspected on the basis of the reduction in pain associated with migraine headaches, spasmodic torticollis, and chronic myofascial pain [10][11][12]. Welch et al observed that various botulinum toxins inhibited release of neuropeptides from rat dorsal root ganglia [13], and Jabbari et al reported that multiple subcutaneous BTX-A injections relieved segmental burning pain [14].…”
Section: Discussionmentioning
confidence: 99%
“…A peripheral antinociceptive effect of the neurotoxin has been suspected on the basis of the reduction in pain associated with migraine headaches, spasmodic torticollis, and chronic myofascial pain [10][11][12]. Welch et al observed that various botulinum toxins inhibited release of neuropeptides from rat dorsal root ganglia [13], and Jabbari et al reported that multiple subcutaneous BTX-A injections relieved segmental burning pain [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported to be effective in the therapy for migraine [4,5] or chronic migraine [6][7][8]. On analogy to migraine, during CH attacks an activation of the trigemino-vascular system and an elevation of calcitonin gene-related peptide (CGRP) in the jugular venous blood [9] have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, patients were injected with 75-100 U BoNT-A (Botox; Allergan, Irvine, USA) at the referred pain sites. We followed the dosing guide per single muscles as suggested by basic Siberstein [8] and the protocol "fixed sites fixed doses" (FSFD) with a maximun BoNT-A dosage of 100 U per session. BoNT-A was reconstituted and diluted in sterile saline at a concentration of 100 U/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Botulinum toxin type A (BoNT-A) is a focally acting neurotransmitter from presynaptic nerve endings at the neuromuscular junction that results in muscle relaxation. Treatment with BoNT-A is a safe and efficacious treatment of CTH and migraine [6][7][8]. Although its mechanism of action in headache disorders is unknown, BoNT-A may have antinociceptive effects apart from its muscle-relaxing actions [9].…”
Section: Introductionmentioning
confidence: 99%